1988
DOI: 10.1002/ajh.2830290304
|View full text |Cite
|
Sign up to set email alerts
|

Probable genetic linkage between genes coding for platelet‐specific antigens of the PIA and bak systems

Abstract: Studies of the inheritance of the platelet-specific alloantigens PlA1/PlA2 and Baka/Bakb in informative families provided evidence that the genes determining PlA and Bak antigens are in close genetic linkage (P = .004). In 154 normal, unrelated Caucasian subjects it was found that the antigen PlA1 is associated with Baka and the antigen PlA2 with Bakb more often than would be expected by chance (P less than .05). Bak and PlA antigens are carried on platelet membrane glycoproteins IIb and IIIa, respectively, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However the occurrence of the second polymorphism associated with HPA‐1b (T→G codon 40 in GPIIIa), as described by Perichon et al ( 7), was not observed in this panel of individuals. Nor has a potential linkage desequilibrium between HPA‐1 and 3, as suggested by Letellier et al ( 9), been observed to any significant degree in this population.…”
Section: Allele Frequencies In Different Populationsmentioning
confidence: 58%
“…However the occurrence of the second polymorphism associated with HPA‐1b (T→G codon 40 in GPIIIa), as described by Perichon et al ( 7), was not observed in this panel of individuals. Nor has a potential linkage desequilibrium between HPA‐1 and 3, as suggested by Letellier et al ( 9), been observed to any significant degree in this population.…”
Section: Allele Frequencies In Different Populationsmentioning
confidence: 58%
“…It should be noted that, apart from HPA‐1, other polymorphisms might be of clinical significance with respect to thrombogenicity (Gonzalez‐Conejero et al , 1998; Carter et al , 1999; Kroll et al , 2000). Furthermore, HPA‐1 could be in linkage disequilibrium with other gp polymorphisms, which might themselves have an effect on platelet function (Letellier et al , 1988). In this sense, platelet thrombogenicity in a given individual reflects, among other factors, the result of a multitude of underlying combinations and interactions of gp polymorphisms.…”
mentioning
confidence: 99%